2011
DOI: 10.1055/s-0031-1289168
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis of Digital Arteries Associated with Tamoxifen Use: Case Report

Abstract: Arterial thrombosis in the upper extremity occurs often at the wrist. We report a unique case of thrombosis that involved multiple digital arteries, without radial or ulnar artery involvement, which developed only after using tamoxifen despite chronic occupational blunt percussive hand use. Revascularization was achieved after thrombectomy. Multiple digital arterial thromboses may complicate the use of tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Thus, we cannot rule out the possibility that venous thrombosis was caused by prednisolone. However, there are more reports mentioning the risks of arterial thromboembolism associated with tamoxifen than with steroid, so we considered tamoxifen as a more significant causative agent than prednisolone [9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot rule out the possibility that venous thrombosis was caused by prednisolone. However, there are more reports mentioning the risks of arterial thromboembolism associated with tamoxifen than with steroid, so we considered tamoxifen as a more significant causative agent than prednisolone [9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Richard et al reported that a 55-year-old man developed digital artery thrombosis after using tamoxifen to treat mesenteric panniculitis for 1 week. After embolectomy, the blood flow was successfully reconstructed [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thrombotic complications, mainly venous but occasionally also arterial, represent the main complication. [63][64][65][66][67] The compound has been also demonstrated to trigger the appearance of VTE in asymptomatic participants with congenital thrombophilia, even though there is no sure evidence for a summation of effects. 63 The mechanism of action is unclear.…”
Section: Tamoxifen and Similar Compoundsmentioning
confidence: 99%